Generation and analysis of novel Reln‐deleted mouse model corresponding to exonic Reln deletion in schizophrenia. Issue 5 (5th March 2020) - Sawahata, Masahito; Mori, Daisuke; Arioka, Yuko; Kubo, Hisako; Kushima, Itaru; Kitagawa, Kanako; Sobue, Akira; Shishido, Emiko; Sekiguchi, Mariko; Kodama, Akiko; Ikeda, Ryosuke; Aleksic, Branko; et al.
Abstract : Aim: A Japanese individual with schizophrenia harboring a novel exonic deletion in RELN was recently identified by genome‐wide copy‐number variation analysis. Thus, the present study aimed to generate and analyze a model mouse to clarify whether Reln deficiency is associated with the pathogenesis of schizophrenia. Methods: A mouse line with a novel RELN exonic deletion ( Reln ‐del) was established using the CRISPR/Cas9 method to elucidate the underlying molecular mechanism. Subsequently, general behavioral tests and histopathological examinations of the model mice were conducted and phenotypic analysis of the cerebellar granule cell migration was performed. Results: The phenotype of homozygous Reln ‐del mice was similar to that of reeler mice with cerebellar atrophy, dysplasia of the cerebral layers, and abrogated protein levels of cerebral reelin. The expression of reelin in heterozygous Reln ‐del mice was approximately half of that in wild‐type mice. Conversely, behavioral analyses in heterozygous Reln ‐del mice without cerebellar atrophy or dysplasia showed abnormal social novelty in the three‐chamber social interaction test. In vitro reaggregation formation and neuronal migration were severely altered in the cerebellar cultures of homozygous Reln ‐del mice. Conclusion: The present results in novel Reln ‐del mice modeled after our patient with a novel exonic deletion in RELN are expected to contribute to the development of reelin‐based therapies for schizophrenia.